2014
DOI: 10.1002/ajmg.a.36390
|View full text |Cite
|
Sign up to set email alerts
|

Keutel syndrome: Report of two novel MGP mutations and discussion of clinical overlap with arylsulfatase E deficiency and relapsing polychondritis

Abstract: Keutel syndrome is a rare, autosomal recessive disorder characterized by diffuse cartilage calcification, peripheral pulmonary artery stenosis, midface retrusion, and short distal phalanges. To date, 28 patients from 18 families have been reported, and five mutations in the matrix Gla protein gene (MGP) have been identified. The matrix Gla protein (MGP) is a vitamin K-dependent extracellular protein that functions as a calcification inhibitor through incompletely understood mechanisms. We present the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…A novel homozygous MGP mutation (c.61 + 1G > A) in a patient with KS without signs of arterial calcification has also described [Cranenburg et al, ]. Recently a new MGP mutation (c.79G > T, which predicts p.E27X) and a partial deletion of exon 4 has reported [Weaver et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…A novel homozygous MGP mutation (c.61 + 1G > A) in a patient with KS without signs of arterial calcification has also described [Cranenburg et al, ]. Recently a new MGP mutation (c.79G > T, which predicts p.E27X) and a partial deletion of exon 4 has reported [Weaver et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…However, literature review revealed only 10 patients with molecular diagnosis [Munroe et al, 1999;Hur et al, 2005;Cranenburg et al, 2011;Weaver et al, 2014;Tüysüz et al, 2015;Bayramoğlu et al, 2016]. These patients shared 7 distinct pathogenic variants: 3 were donator or acceptor splice site type (IVS1-2A>G/c.62-2A>G; IVS2+1G>A; IVS1+1G>A/c.61+1G>A), 3 were deletion variants [1 missense (c.113T>A), 1 nonsense (c.79G>T; p.Glu27X), and 1 frameshift (c.69delG)], and 1 was a partial deletion of exon 4.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the abnormalities seen in Keutel syndrome are also common in chondrodysplasia punctata and warfarin embryopathy (Franco et al., ; Munroe et al., ; Wainwright & Beighton, ). Although it is known that the inactivation of arylsulfatase E (ARSE) leads to chondrodysplasia punctata, the actual substrate and function of this enzyme are still unknown (Weaver et al., ). It has been suggested that mutation in ARSE leads to impaired vitamin K metabolism, which in turn inhibits the gamma‐glutamyl carboxylation of Gla proteins including MGP (Herman & Siegel, ).…”
Section: Midface Hypoplasia Caused By Abnormal Cartilage Calcificatiomentioning
confidence: 99%
“…Although it was reported that warfarin, a commonly used anticoagulant, may inhibit ARSE in vitro (Franco et al., ), the primary pharmacological target of warfarin in vivo is the vitamin K epoxide reductase (VKORC1), an enzyme that recycles oxidized vitamin K1 to its reduced form after it has participated in the gamma‐carboxylation of the Gla proteins. This explains the prevalence of Keutel syndrome‐like craniofacial abnormalities in the babies born to pregnant mothers treated with warfarin or similar anticoagulant agents (Howe, Webster, Lipson, Halliday, & Sheffield, ; Rost et al., ; Weaver et al., ). Further supporting the pathophysiological link between gamma‐carboxylation and MGP, it was recently reported that patients with a mutation in the gene encoding the gamma‐glutamyl carboxylase (GGCX) are also often characterized by midface hypoplasia (Watzka et al., ).…”
Section: Midface Hypoplasia Caused By Abnormal Cartilage Calcificatiomentioning
confidence: 99%
See 1 more Smart Citation